2018
DOI: 10.1101/507780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human microbiome aging clocks based on deep learning and tandem of permutation feature importance and accumulated local effects

Abstract: The human gut microbiome is a complex ecosystem that both affects and is affected by its host status. Previous analyses of gut microflora revealed associations between specific microbes and host health and disease status, genotype and diet. Here, we developed a method of predicting biological age of the host based on the microbiological profiles of gut microbiota using a curated dataset of 1,165 healthy individuals (3,663 microbiome samples). Our predictive model, a human microbiome clock, has an architecture … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 96 publications
(60 reference statements)
1
46
0
Order By: Relevance
“…However, the variation in gut microbiome between populations, as a result of differences in geography, life style, diet, age, genetics and possible other factors has been reported to be more extensive than the variation between males and females [57]. Published literature regarding the effect of age on the gut microbiota indicates that whereas the gut microbiome is very dynamic with increasing microbial diversity in the early years of life, the gut microbiota in healthy adults is relatively stable [58] albeit recent studies do indicate that the gut microbiota can serve as a chronological marker [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…However, the variation in gut microbiome between populations, as a result of differences in geography, life style, diet, age, genetics and possible other factors has been reported to be more extensive than the variation between males and females [57]. Published literature regarding the effect of age on the gut microbiota indicates that whereas the gut microbiome is very dynamic with increasing microbial diversity in the early years of life, the gut microbiota in healthy adults is relatively stable [58] albeit recent studies do indicate that the gut microbiota can serve as a chronological marker [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…As well, age‐thresholds, if any, for other microbiota products need to be established and reasoned. Waiting for these issues to be further evaluated, a recent investigation demonstrated that some bacteria are important in predicting age, as the abundance and loss of certain bacteria associated with person's lifetime (Galkin et al, ). We thus think that the tryptophan deficiency from a certain age may be associated to the co‐occurring changes in microbial composition and ecological interactions within the gut.…”
Section: Discussionmentioning
confidence: 99%
“…These results from both mice and humans suggested that gut microbiota is relatively stable in younger adulthood and it will become more unsteady after entering older age. Recently, researchers studying the gut bacteria of thousands of people found the microbiome could be used as a biological age clock to predict the age according to machine learning [38]. Research on age-dependent patterns of gut microbial diversity in human adults found a strong association between age and alpha diversity was kept until 40 years old [39].…”
Section: Discussionmentioning
confidence: 99%